EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen